Right Heart Failure With Recurrent Pericardial Effusion Mimicking Effusive-Constrictive Pericarditis Several Years After Renal Transplantation - Andres Cordova Sanchez MC; Mostafa Vasigh MD; Ravi Singh MBBS; Adriana May MD; Mehdi Marvasti MD; Sakti Pada Mookherjee MD (SAGE Publishing, 2022)
Pericardial disease is a rare complication after renal transplantation. We present a patient who developed high-output cardiac failure from a large arteriovenous (AV) fistula with recurrent pericardial effusion resulting in a constrictive hemodynamic pattern that was revealed during cardiac catheterization. Pericardiectomy was considered for recurrent effusive pericarditis, but per cardiac surgery recommendations, closure of the AV fistula dramatically cured the patient's heart failure, and no recurrence of pericardial effusion was seen during follow-up almost a year later.